Effect of platelet-rich plasma on alveolar bone repair following impacted third molar surgery evaluated to Cone Beam computerized tomography - Quincho-Rosales, Dilmer A. (2021)
Introduction: Platelet-rich plasma (PRP) is a biomaterial with a high platelets concentration and growth factors enhance tissue regeneration after application in surgical procedures, such as third molar extraction. Material and methods: The study was performed with 20 patients with indication for third bilateral lower molar extraction. The extraction were performed in the same surgical time and one of them the PRP gel was applied (randomly chose) and the other as control group. The postoperative evaluation was carried out until three and a half months, the parameters evaluated were: postoperative pain and wound and bone density using Cone Beam computed tomography. Results: Postoperative pain during the third day, first and second week was lower grade than sites of PRP application to the control group (p <0.05). The bone density measured by Cone Beam CT was higher at the sites of PRP application than the control group (p <0.05). Conclusion: PRP has an effect in reducing postoperative pain and accelerating wound healing, and it also shows higher bone density compared to not applying PRP.